2015
DOI: 10.1007/s12257-014-0885-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel low-molecular weight alkaline mannanase from Streptomyces tendae

Abstract: A novel, low-molecular weight, alkaline mannanase from Streptomyces tendae (MnSt) was purified to homogeneity and biochemically characterized. The extracellular mannanase was purified with 26.3% yield using a Sepharose Cl-6B column. The molecular mass of MnSt was approximately 24 kDa. MnSt was stable over a broad pH range (5 ~ 12.5), was thermally stable at 60°C, and functioned optimally at 50°C and a pH of 12.0. MnSt had K m and V max values of 0.05 ± 1 mg/mL and 439 ± 0.5 mmol/min, respectively, using bean g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(65 reference statements)
1
7
0
2
Order By: Relevance
“…The same optimum pH has been reported by Titapoka et al [46]; Mabrouk and Ahwany [28]; Mou et al [33]; Kim et al [24]; Chandra et al [9] and Zhang et al [39]. Meanwhile, Lu et al [27]; Yoo et al [52]; Yang et al [51] and Wang et al [50] reported different optimum pH at 11, 4, 5.5 and 5.…”
Section: Effects Of Ph and Temperaturesupporting
confidence: 77%
See 2 more Smart Citations
“…The same optimum pH has been reported by Titapoka et al [46]; Mabrouk and Ahwany [28]; Mou et al [33]; Kim et al [24]; Chandra et al [9] and Zhang et al [39]. Meanwhile, Lu et al [27]; Yoo et al [52]; Yang et al [51] and Wang et al [50] reported different optimum pH at 11, 4, 5.5 and 5.…”
Section: Effects Of Ph and Temperaturesupporting
confidence: 77%
“…While Cu 2+ , Zn 2+ and Ni 2+ ions only decrease the activity of mannanase up to 20-30%. The property of Co 2+ ions as activators have been reported by Yoo et al [52] who reported that increasing of activity of mannanase from S. tendae was up to 63%. Yang et al [51] reported that the Co 2+ ions enhanced the activity of mannanase from Neosartorya fischeri up to 10-13%.…”
Section: Effects Of Metal Ionsmentioning
confidence: 58%
See 1 more Smart Citation
“…The released reducing sugars were measured using the 3,5‐dinitrosalicyclic (DNS) method with LBG as the substrate against a standard curve of mannose . An appropriately diluted enzyme (100 µl) was mixed with 1% (w/v) LBG (100 µl) in 10 mM KCl/NaOH buffer (pH 12.5) and incubated at 60 °C for 30 min in a water bath, and then 100 µl DNS reagent was added and boiled for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Tidak banyak penelitian yang melaporkan enzim mananase alkali dari bakteri laut, terutama dari perairan Indonesia. Mannanase alkali banyak dilaporkan diproduksi dari Bacillus (Hatada et al, 2005) dan Streptomyces (Yoo et al, 2015;Pradeep et al, 2016) (2014) mengisolasi Bacillus manolitik dari air laut di Pul au Pari, DKI Jakarta untuk produksi manooligosakarida. Potensi mananase alkali sangat luas, seperti dimanfaatkan oleh industri deterjen dan kertas karena sebagian besar proses di industri tersebut dilakukan di pH tinggi (Chauhan, Puri, Sharma, & Gupta, 2012;Dhawan & Kaur, 2007;Hatada et al, 2005).…”
Section: Nilai Ph Dan Suhu Optimal Reaksi Enzim Xilanase Dan Mananaseunclassified